2015
DOI: 10.1097/gme.0000000000000382
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index continues to accurately predict percent body fat as women age despite changes in muscle mass and height

Abstract: Surprisingly, the effects of changes in height and lean body mass balance each other out in BMI calculation. There continues to be a strong correlation between BMI and %BF in adult women as they age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…If BN was associated with lower percentage of body fat in prior studies, this could easily produce differences in leptin. However, most previous studies have controlled for BMI, which is generally highly correlated with body fat (e.g., Ablove, Binkley, Leadley, Shelton, & Ablove, 2015; Heymsfield et al, 2014) and was in the current sample ( r =.79–.86). Thus, this explanation of non-replication seems unlikely.…”
Section: Discussionmentioning
confidence: 68%
“…If BN was associated with lower percentage of body fat in prior studies, this could easily produce differences in leptin. However, most previous studies have controlled for BMI, which is generally highly correlated with body fat (e.g., Ablove, Binkley, Leadley, Shelton, & Ablove, 2015; Heymsfield et al, 2014) and was in the current sample ( r =.79–.86). Thus, this explanation of non-replication seems unlikely.…”
Section: Discussionmentioning
confidence: 68%
“…BMI can even be used as adiposity proxy, especially in population studies with large samples or in other situations where there is a need for simple, practical and inexpensive methods. 19 Studies have shown that the magnitude of the prediction error of body fat by BMI in older adults is comparable with other doubly indirect methods, showing that its use at the population level produces relatively acceptable estimates. 20 The use of BMI in older adults can result in overweight and obesity classification errors as a result of inaccuracies and difficulties of measuring the height and lean body mass reduction that occurs during aging.…”
Section: Discussionmentioning
confidence: 92%
“…18 Weight, BMI and hip circumference were variables strongly correlated with the factor 1 (global adiposity pattern). 19 Hip circumference could be used as an indicator of total body adiposity, especially in situations where it is not possible to measure the weight and height, but its use is limited because there are no parameters for its classification. BMI can even be used as adiposity proxy, especially in population studies with large samples or in other situations where there is a need for simple, practical and inexpensive methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlations between BMI and more direct measures of body fatness are generally strong (r>0.70). [1][2][3][4] Observational studies have shown that people who do comparatively more physical activity have a lower BMI than less active people. 5 6 Few large epidemiological studies have directly estimated body fatness, and it is of interest to examine whether more comprehensive measures of body fatness provide additional information above and beyond that which is captured by BMI.…”
Section: Introductionmentioning
confidence: 99%